Microbial emission levels and diversities from different land use types - Li, Xinyue; Chen, Haoxuan; Yao, Maosheng (Environment international, 2020)
•Different land-use types have varying levels and diversities of microbial emissions.•Street land types in Beijing emitted Massilia with a relative abundance of over 80%.•Human activities could substantially affect the airborne microbiota. Bioaerosol particles, originated from many different earth ground sources, have unique health impacts, including respiratory infections, allergic reactions, and toxic effects. Here, we applied a portable high-flow sampler HighBioTrap to collect and investigate bioaerosol emissions from 13 different land types (forest, wetland, lake, bare soil, cropland, wastewater treatment facility, street, livestock farm, smeltery and garden) that are heavily or less affected by humans. Plate cultivation, real-time quantitative PCR analysis (q-PCR) and high-throughput gene sequencing analysis were used to characterize bacterial and fungal levels as well as their community structures emitted from different land use types. Results showed that there were statistically significant differences in biological emission levels (up to 100-fold difference) and diversity among different land use types. Cropland, sewage plant street and smeltery heavily affected by human activities were found to exhibit higher bioaerosol emission levels, with Massilia genus detected as the dominant species. In contrast, some land types (lakes, forests, gardens, and wetland) less affected by humans were found to emit lower bioaerosol levels but with higher culturability, e.g., up to 16% for wetland. In addition, the microbiological structures of these land-use types usually had higher species richness and diversity, yet different dominant species. For some land types such as streets in Beijing, the microbial community appeared to be skewed with an over 80% relative abundance of a specific dominant species such as Massilia. Other detected dominant species also included Acinetobacter and Brevundimonas for street, and Sphingomonas for wetland. For fungal community, Naganishia, Alternaria, Penicillium, and Aureobasidium were detected to be most abundant. RDA analysis showed metals and ions could to some extent affect the microbial community structures. This work highlights that the human activities could substantially affect the airborne microbiota, which in turn could affect local human health and ecosystems. On the other hand, the results here provide important references for quantitatively estimating the microbial emissions from the earth into the atmosphere.